Analisis Fundamental Makro Struktur Modal Terhadap Nilai Perusahaan dengan Struktur Kepemilikan, Manajemen Laba dan Kinerja Keuangan sebagai Variabel Intervening pada Perusahaan Makanan dan Minuman - Pranata, Natasha Anjanette; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
The industrial world and businesses are developing at a very fast pace, which makes competition fierce. This study aims to analyze the macro influence of capital structure on corporate value in food and beverage companies, by considering ownership structure, profit management, and financial performance as intervening variables. The results of the study show that the macro capital structure has a significant effect on the value of companies in food and beverage companies. In addition, ownership structure, profit management, and financial performance also play a role as intervening variables that affect the relationship between the macro capital structure with the company's value. The implication of this study is the importance of paying attention to these factors in optimizing the company's value in the food and beverage sector.